Issues concerning Landowner Management Plan Adoption Decisions: A Recursive Bivariate Probit Approach - Omkar Joshi; Donald L. Grebner; Ian A. Munn; Robert K. Grala (International Journal of Forestry Research)
Despite the likely benefits of having a written forest management plan, a small number of landowners in the United States have the one. A recursive bivariate probit model was used to identify the possible relationship between landowners’ decision to obtain a management plan and their interest in future timber harvesting. Our study results based on recursive bivariate model suggest that landowners having larger land ownerships, longer forest ownership tenure, and higher education were more likely to have a forest management plan and future timber harvesting interest. While the landowners having interest for wildlife management were also interested to have a written management plan, they did not prefer to harvest in future. Study results indicate that written management plan means more than a timber harvesting strategy to landowners in general. Many elderly landowners with a low level of income and less formal education and those having small or medium sized tracts of forestland are less likely to own a written management plan. Therefore, this group requires special attention in various government sponsored forest management related extension activities. Future research on understanding landowner perception behind written management plan is recommended.